Математическое моделирование режимов транспорта газа через локальную подсистему c модифицированной моделью газоперекачивающего агрегата - Гурковский, П. Е. (ХНУРЕ, 2012)
This work is devoted to creation of a new model of gas transportation by means of local subsystems. A new model of gas temperature and compression coefficient calculation is proposed.
Keywords: газотранспортная система; САУ-А; газоперекачивающий агрегат